2018
DOI: 10.9734/ajrcs/2018/41549
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters, Multivariate Analysis and Tolerance Indices of Rice Genotypes under Normal and Drought Stress Environments

Abstract: In order to evaluate genetic parameters and drought tolerance indices using multivariate analysis, seventeen genotypes of rice were evaluated under normal and drought conditions. The combined analysis of variance indicated highly significant effects of genotype on all studied traits under normal and drought conditions. Most studied genotypes were better than the grand mean during normal and drought conditions. Drought stress reduced the studied traits while other was tolerant to drought, suggesting genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
(32 reference statements)
5
7
0
1
Order By: Relevance
“…According to combined ANOVA analysis of nonstress (Yp) and stress (Ys) conditions as well as drought tolerance indices (Table 5), grain yield (Yp and Ys) and all drought tolerance indices exhibited highly significant between genotypes (G). El-Hashash and EL-Agoury [37] had previously found similar findings. The findings demonstrated that almost all indices showed a significant genetic variation and could distinguish between genotypes under stress and non-stress conditions.…”
Section: Analysis Of Variancesupporting
confidence: 70%
See 2 more Smart Citations
“…According to combined ANOVA analysis of nonstress (Yp) and stress (Ys) conditions as well as drought tolerance indices (Table 5), grain yield (Yp and Ys) and all drought tolerance indices exhibited highly significant between genotypes (G). El-Hashash and EL-Agoury [37] had previously found similar findings. The findings demonstrated that almost all indices showed a significant genetic variation and could distinguish between genotypes under stress and non-stress conditions.…”
Section: Analysis Of Variancesupporting
confidence: 70%
“…Therefore, those drought tolerance indices were not influenced mainly by year effect. El-Hashash and EL-Agoury [37] reported that a highly significant variation was observed in grain yield and tolerance indices among the studied rice genotypes, while, there were no significant differences between the two study years in terms of grain yield and tolerance indices. Saad et al [39] mentioned that significant differences were observed between years and genotypes for most studied drought indices.…”
Section: Analysis Of Variancementioning
confidence: 80%
See 1 more Smart Citation
“…In general, the grain yield ranged between 6.34 and 9.55 t ha -1 , the promising lines RGA-13 and RGA-14 had the highest grain yield, 9.31 and 9.55 t ha -1 . This conclusion supported the use of a stress tolerance index to reflect genotypes behavior under stress and normal conditions (Benmahammed et al, 2010;El-Hashash et al, 2018). Selection based on just yield is ineffective, whereas selection based on yield and its components is more efficient.…”
Section: Mean Performance Of Combined Analysismentioning
confidence: 59%
“…Variabel yang diamati meliputi tinggi tanaman, diameter batang, panjang akar, volume akar, bobot segar akar, bobot kering akar, bobot segar tanaman, bobot kering tanaman. Penentuan ITC dilakukan menggunakan rumus sebagaimana dalam penelitian El-Hashash et al (2018).…”
Section: Penentuan Indeks Toleransi Terhadap Cekaman (Itc)unclassified